Effects of Socioeconomic Status, Parent–Child Relationship, and Learning Motivation on Reading Ability - Chen, Qishan; Kong, Yurou; Gao, Wenyang; Mo, Lei (Frontiers in Psychology, 2018)
Against the background of Chinese culture, we investigated the relationship between family socioeconomic status (SES) and children’s reading ability. Participants included 2294 middle-school students in grade 8. SES was measured by parents’ education level, parents’ occupational prestige and family property, and children’s reading ability was estimated with item response theory. In addition, we adopted an 8-item parent-child relationship scale and a 22-item learning motivation scale that included four dimensions. We examined whether the parent-child relationship mediated the relationship between family SES and reading ability and whether this was moderated by learning motivation. The results indicated that the parent-child relationship played a mediating role in the relationship between SES and reading ability. This relationship was moderated by students’ learning motivation. The direct effects of SES on reading ability at high, medium and low levels of learning motivation were .24, .32 and .40, respectively.